Endonuclease domain of the Drosophila melanogaster R2 non-LTR retrotransposon and related retroelements: a new model for transposition - Mukha, Dmitry V.; Pasyukova, Elena G.; Kapelinskaya, Tatiana V.; Kagramanova, Arina S. (Frontiers in Genetics, 2013)
The molecular mechanisms of the transposition of non-long terminal repeat (non-LTR) retrotransposons are not well understood; the key questions of how the 3’-ends of cDNA copies integrate and how site-specific integration occurs remain unresolved. Integration depends on properties of the endonuclease (EN) domain of retrotransposons. Using the EN domain of the Drosophila R2 retrotransposon as a model for other, closely related non-LTR retrotransposons, we investigated the EN domain and found that it resembles archaeal Holliday-junction resolvases. We suggest that these non-LTR retrotransposons are co-transcribed with the host transcript. Combined with the proposed resolvase activity of the EN domain, this model yields a novel mechanism for site-specific retrotransposition within this class of retrotransposons, with resolution proceeding via a Holliday junction intermediate.